Coffee intake and risk of diabetic nephropathy: a Mendelian randomization study - Fang, Jiaxi; Song, Kai; Zhang, Di; Liang, Yan; Zhao, Huan; Jin, Juan; He, Qiang (Frontiers in Endocrinology, 2023)
Rationale & Objective: A causal relationship concerning coffee intake and diabetic nephropathy (DN) is controversial. We conducted a Mendelian randomization study to assess the causal nature of these associations. Methods: 40 independent single nucleotide polymorphisms (SNPs) associated with coffee intake were selected from the UK Biobank study. Summary-level data for diabetic nephropathy were obtained from publicly available genome-wide association studies (GWAS)and the FinnGen consortium. Inverse variance weighted (IVW), MR-Egger, and weighted median (WM) methods were used to examine a causal association. Sensitivity analyses included Cochran’s Q test, the intercept of MR-Egger, MR-PRESSO, and the Outlier method. Leave-One-Out sensitivity analyses were also conducted to reduce the heterogeneity. Results: Our current study demonstrated positive associations of genetically predicted coffee intake with diabetic nephropathy (OR=2.4212; P = 0.0088), type 1 diabetes with renal complications (OR = 3.3185; p = 0.0447), and type 2 diabetes with renal complications (OR = 2.4481, P= 0.0173). These findings were robust across several sensitivity analyses. Conclusions: Using genetic data, this study reported a positive correlation between coffee intake and the risk of diabetic nephropathy. However, subgroup analysis on coffee intake, including brewing method, type of coffee, and quantity, is needed for a more accurate and reliable conclusion.